Everyday violence and bottom-up peace building initiatives by the urban poor in Mumbai. Issue 1 (January 2020) - Bhide, Amita
Abstract : While there has been some research that points to the 'everyday' violence in informal settlements that house some of the most marginalised communities in cities of the global South, as much attention has not been paid to the simultaneous presence of peace and inclusion-directed activities. This paper is an attempt to understand peace-making in a context of entrenched violence through the story of inhabitants of Mandala, an informal settlement in Mumbai. I argue that the urban poor are not passive victims of violence but that they express their agency in living with violence. Living with violence also involves several invisible moves to build footholds in the city, being resilient to the everyday violence and engaging in a politics of hope. Such invisible actions gain more traction and take the form of greater assertion for inclusion and peace building if accompanied by self-empowerment and a sense of movement in their lives. Critically, peace building is integrally linked to greater assertions towards claim-making in the city; peace without such assertions makes little difference to the everyday experience of violence faced by communities.